Early Detection of Mental Health in Stikes Panrita Husada Bulukumba Students (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2024)
Background: Mental health problems in the modern era can arise due to various pressures in life. Currently the world is entering a demographic transition where the adolescent population in 2019 reached 1.2 billion worldwide or around 16 percent of the world's population and increased to 16.2 percent of the total world population in 2020 (UNICEF, 2019; Worldometer, 2020 ). Data from the World Health Organization (WHO) shows that almost 1 billion people in the world live with mental disorders and every 40 seconds one person dies by suicide (Ingrid et al., 2020).Objective: To determine early detection of mental health in STIKes Panrita Husada Bulukumba students. With a sample size of 384 people. Method: This research uses a quantitative research design with descriptive research methods. With a total of 96 respondents, students at levels 2 and 3 were selected who met the criteria and used questionnaire sheet media (bitly/googlefrom) for the data collection process. Research Results: The most respondents with a normal level of mental health were 82 people (85.4%), respondents who experienced the lowest level of mental health were borderline with a total of 6 people (6.3%) and respondents who experienced an abnormal level of health with a total of 8 people (8.3%). Conclusions : Based on research conducted on level 2 and 3 students of Stikes Panrita Husada Bulukumba, data was obtained that the majority of students did not experience mental health problems.